Amidato complexes of ruthenium, rhodium and iridium from concise N–H bond activation: exploration in catalysis. Issue 26 (1st July 2015) - Romero, R. Martín; Fra, Laura; Lishchynskyi, Anton; Martínez, Claudio; Streuff, Jan; Muñiz, Kilian
Abstract: Acceptor-substituted N–H groups as found in carbamides and sulfonamides are readily activated through suitable unsaturated metal complexes applying the concept of metal–ligand bifunctionality. This process constitutes the basis for an enantioselective intramolecular addition of N–H groups onto activated alkenes. The resulting compounds can also be employed as catalyst precursors for transferhydrogenation. Graphical abstract: